2021
DOI: 10.3390/toxins13100693
|View full text |Cite
|
Sign up to set email alerts
|

EGCG Alleviates Oxidative Stress and Inhibits Aflatoxin B1 Biosynthesis via MAPK Signaling Pathway

Abstract: Aflatoxin biosynthesis has established a connection with oxidative stress, suggesting a prevention strategy for aflatoxin contamination via reactive oxygen species (ROS) removal. Epigallocatechin gallate (EGCG) is one of the most active and the richest molecules in green tea with well-known antioxidant effects. Here, we found EGCG could inhibit aflatoxin B1 (AFB1) biosynthesis without affecting mycelial growth in Aspergillus flavus, and the arrest occurred before the synthesis of toxin intermediate metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Our results indicated that the shacking speed process produced an additive effect in binding aflaM1. This result is in parallel with the work of (Adunphatcharaphon et al, 2020;Saeed, Naveed, et al, 2017;Xu et al, 2021) that mentioned that the removal strategy for aflatoxin contamination by GTL was very effective due to its high content of catechin and EGCG. EGCG is one of the most active and richest molecules in GTL because it was reported as a vigorous antioxidant (Xu et al, 2021).…”
Section: Cow Milk Samplesupporting
confidence: 80%
“…Our results indicated that the shacking speed process produced an additive effect in binding aflaM1. This result is in parallel with the work of (Adunphatcharaphon et al, 2020;Saeed, Naveed, et al, 2017;Xu et al, 2021) that mentioned that the removal strategy for aflatoxin contamination by GTL was very effective due to its high content of catechin and EGCG. EGCG is one of the most active and richest molecules in GTL because it was reported as a vigorous antioxidant (Xu et al, 2021).…”
Section: Cow Milk Samplesupporting
confidence: 80%
“…Similar to the regulatory network orchestrating the carbon and nitrogen metabolisms of aflatoxigenic fungi, further elements of the environmental stress response system and their regulation should be revealed and considered as future targets to control the growth and AF production of these molds. Actually, there is a plethora of literature data demonstrating the efficiency of various antioxidants to hinder the AF production by aflatoxigenic fungi ( Reverberi et al, 2005 , 2006 ; Zjalic et al, 2006 ; Caceres et al, 2017 ; Zhao et al, 2018 ; Xu et al, 2021 ). Obviously, a deeper understanding of the regulatory elements interweaving the pathways responsible for the proper adjustment and co-regulation of mycotoxin production and environmental stress response may also help us to develop novel technologies for mycotoxin contamination control.…”
Section: Genetics Of Aflatoxin Productionmentioning
confidence: 99%
“…Oxidative stress is one of the critical molecular mechanisms of adverse effects caused by many toxic chemical hazards or drugs (e.g., heavy metals, mycotoxins, pesticides, chemotherapy drugs, and antibiotics) [ 88 ]. Multiple studies reported that AFB1 and its derivatives could trigger oxidative stress by inducing the formation of ROS or decreasing intracellular antioxidants or the activities of antioxidant enzymes [ 36 , 70 , 73 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. In the liver tissues, the cytochrome (CYP)1A2 and CYP3A4 could bio-transform into AFBO, which is a harmful and extremely active, electrophilic metabolite.…”
Section: Curcumin’s Protective Role In Preventing Afb1-induced Toxici...mentioning
confidence: 99%